Daily hassle effects on daily cigarette and/or e-cigarette use: the moderating effect of daily uplifts - Lin, Yitong; B O’Connor, Daryl; Conner, Mark (Annals of behavioral medicine, 2025)
Abstract Background Daily hassles, as minor stressful events, are common in life. However, they have received less attention in previous studies on relationships between stressful events and nicotine product use. Meanwhile, daily uplifts have also been investigated less in research on nicotine use. Purpose The current study was conducted to explore the relationships between daily measures of hassles, uplifts, and the use of nicotine products (ie, cigarettes, e-cigarettes). Methods This was a daily diary study. Participants completed 1 diary each day for up to 7 days. One hundred and eighty-one adults who currently use cigarettes or e-cigarettes solely or co-use both completed a total of 886 daily diary entries. Multilevel modeling was used to predict the daily use of the above nicotine products from daily hassles, daily uplifts, and their interactions. Results Daily hassles were positively associated with any daily nicotine use. There were no significant associations between daily hassles and daily cigarette use or between daily hassles and daily e-cigarette use. Daily uplifts were not directly associated with any behaviors, but daily hassles and daily uplifts showed a significant interaction in affecting any daily nicotine use, daily cigarette use, and daily e-cigarette use. In each use pattern, increasing levels of uplifts were associated with an attenuation of the relationship between hassles and the use of nicotine products. Conclusions It may be worthwhile to explore further the effects of daily hassles and daily uplifts on nicotine product use through ecological momentary assessments. Smoking/vaping was more likely on days with more compared to less hassles, although the presence of more daily uplifts removed this effect.